HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PELANGGAN DI LABORATORIUM KLINIK PRODIA BUAH BATU - rohimah, ai titin; pamungkas, gugum (Jurnal Sehat Masada, 2024)
Laboratories are required to improve the quality of service so that customer satisfaction increases. Based on a preliminary study of secondary data on the results of the customer satisfaction index (CSI) in 2021, the results obtained for service CSI were 97.34%, while in 2022 the results obtained were 92.95%, with a CSI target of ≥ 85%. Even though the target has been reached, from this evaluation there is a decrease in CSI results in 2022 of 4.39% compared to 2021, this occurs because there is a decrease in scores related to service quality. The purpose of this study was to determine the relationship between service quality and customer satisfaction at the Prodia Buah Batu Clinical Laboratory. The research design is a quantitative type with a correlative analytic design using a cross sectional approach. The sampling technique used was purposive sampling and obtained 79 respondents. Data analysis using univariate and bivariate, Chi quare test. The results showed that there was a relationship between service quality and customer satisfaction at the Prodia Buah Batu Clinical Laboratory, with a p value = 0.000. Based on the results of the study it can be concluded that the quality of service received by customers can affect the condition of customer satisfaction. It is recommended for the Prodia Buah Batu Clinical Laboratory to improve service quality, especially the Responsiveness aspect and for customer satisfaction, especially the service excellence aspect.